THE INFLUENCE OF WORKFORCE, BUSINESS EXPERIENCE, AND BUSINESS LOCATION ON THE PERFORMANCE OF NAIL ART MSMEs IN PANTAI LABU DISTRICT, DELI SERDANG REGENCY - Nadia Sukawati; Mutawaqil Billah Tumanggor; Melisa Zuriani Hasibuan, Arif Hadian (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to analyze the influence of workforce, business experience, and business location on the performance of Micro, Small, and Medium Enterprises (MSMEs) Nail Art in Pantai Labu District, Deli Serdang Regency. This study uses a quantitative approach with an associative method with a population of 30 respondents also used as research samples through total sampling techniques. Data collection techniques are carried out by distributing questionnaires that have been tested in advance through validity and reliability tests to ensure that the instruments used are feasible and consistent. Furthermore, the data are analyzed using a series of statistical techniques, namely the classical assumption test (normality test, multicollinearity, and heteroscedasticity), multiple linear regression test, partial test (t test), simultaneous test (F test), and analysis of the coefficient of determination (R Square). The results of the study indicate that partially the variables of workforce, business experience, and business location each have a significant effect on the performance of MSMEs with a significance value of 0.000